Is Productive Entrepreneurship Getting Scarcer? A Reflection on the Contemporary Relevance of Baumol's Typology - Maria Minniti; Wim Naudé; Erik Stam (Institute of Labor Economics (IZA), 2023)
We review Baumol's typology of productive, unproductive and destructive entrepreneurship. We argue that the typology is relevant for explaining the secular decline in business dynamics. To the existing explanations for this decline, we put forward the thesis that entrepreneurship has become less productive, due to the unintended effects of entrepreneurship policies adopted widely in Western economies. These have straight-jacketed, distracted and zombified entrepreneurship. Removing these constraints on productive entrepreneurship would require that the decline in level-two institutions, such as democracy and science, be halted and reversed.
Keywords: L26; L21; L53; O40; 330; entrepreneurship; economic growth; economic development; institutions; Baumol